Ghostly intrusion on a frightful Halloween night: a case report of dual valve endocarditis - Margarida Castro; Mariana Tinoco; Rafael Martins; Mário Jorge Amorim; Luísa Pinheiro; Marina Fernandes; Filipa Cardoso; Filipa Almeida; Paulo Pinho; João Português; António Lourenço (Monaldi Archives for Chest Disease)
Multivalvular endocarditis (MVE) is an uncommon presentation and mostly involves mitral and aortic valves. Here, we present a case of an MVE with an unusual and bizarre presentation on a Halloween night with a massive degree of valve destruction and right- and left-side involvement requiring emergent surgery. A 51-year-old male patient with intravenous drug usage presented with anorexia, fever, and dyspnea, rapidly progressing to septic shock with multiorgan dysfunction. Initial blood cultures detected meticillin-sensitive Staphylococcus aureus, and antibiotic therapy was started. Transesophageal echocardiography revealed extensive valve destruction of both mitral and tricuspid valves, namely a mitral valve with large vegetation resembling a ghostly figure, causing severe mitral regurgitation. The patient was transferred for emergent mitral and tricuspid surgery. The particularity of this case, besides the bizarre images, is that, as a drug user, there are specific considerations regarding surgical strategy and options in this scenario that we discussed here.